Mutagenesis of dimeric plasmids by the transposon gamma delta (Tn1000). - Liu, L (1990)
The Escherichia coli F factor mediates conjugal transfer of a plasmid such as pBR322 primarily by replicative transposition of transposon gamma delta (Tn1000) from F to that plasmid to form a cointegrate intermediate. Although resolution of this cointegrate always yields a plasmid containing a single gamma delta insertion, the occasional recovery of transposon-free plasmids after conjugal transfer has led to alternative hypotheses for F mobilization. We show here that gamma delta-free plasmids are found after F-mediated conjugal transfer only when the donor plasmid is a dimer and the recipient is Rec+.